1996
DOI: 10.1002/(sici)1097-0177(199610)207:2<222::aid-aja10>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Neural and skin cell‐specific expression pattern conferred by steel factor regulatory sequence in transgenic mice

Abstract: We have produced transgenic mice expressing a lac2 reporter gene under the control of a fragment of a Steel factor (SLF). The function of this gene is essential for the development of hematopoietic cells, germ cells, melanocytes and pacemaker cells of the intestine. The expression of the transgene, containing 2 kb DNA 5' regulatory sequence, was restricted to neural and skin tissues in appropriate spatial and temporal pattern compared with endogenous SLF mRNA expression. This indicates that the regulatory elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Horizontal serial sections were prepared at 3 μm and stained with Hematoxylin and Eosin (HE). lacZ staining lacZ staining was performed as reported in detail previously (Yoshida et al, 1996b). In brief, cells were fixed for 10 minutes in 2% paraformaldehyde supplemented with 0.2% glutaraldehyde and 0.02% Tween 20.…”
Section: Histologymentioning
confidence: 99%
“…Horizontal serial sections were prepared at 3 μm and stained with Hematoxylin and Eosin (HE). lacZ staining lacZ staining was performed as reported in detail previously (Yoshida et al, 1996b). In brief, cells were fixed for 10 minutes in 2% paraformaldehyde supplemented with 0.2% glutaraldehyde and 0.02% Tween 20.…”
Section: Histologymentioning
confidence: 99%
“…Today it is known that (1) stem cell factor is produced by human (but not mouse) epidermis and (2) stem cell factor supports melanocytic differentiation. [65][66][67][68] Stem cell factor acts by binding to the c-kit receptor, which may be demonstrated in immature and mature melanocytes in animal models. 67 In these studies, c-kit immunopositivity was demonstrated using snap-frozen acetone-fixed tissues and immunofluorescence, a method that is apparently more sensitive than the routine immunoperoxidase methods used on formalin-fixed paraffin-embedded tissue in routine practice in my Department.…”
Section: Part A-embryonic Dermal Melanocytesmentioning
confidence: 99%
“…[14][15][16] Nor is it known how nerves govern fetal skin healing without scarring. 17 It has been suggested that nerve sheath stem cells for melanocytes arrive in the skin during the process of embryonic cutaneous innervation, where exposure to epidermal stem cell factor induces melanocytic differentiaton via the c-kit receptor 16,18 (Appendix, Diagram 2). Nerve growth factor, basic fibroblast growth factor, and other substances may also play a role.…”
Section: Introductionmentioning
confidence: 99%